Fostering uptake: lessons from climate change vulnerability assessments in Africa and Latin America. Issue 4 (19th May 2017) - Wood, Lynnette; Apotsos, Alex; Caffrey, Patricia; Gibbs, Kenneth
ABSTRACT: Findings from climate change vulnerability assessments can inform decision-makers in their evaluation of options to reduce the negative impacts of climate change. Certain attributes of an assessment can improve the use or uptake of its results. The science policy literature describes three characteristics – credibility, salience, and legitimacy – as being necessary for the uptake of scientific results for decision-making. We draw from the experiences of eight climate change vulnerability assessments conducted in Africa and Latin America for USAID (United States Agency for International Development) to explore the practical application of these three characteristics to fostering uptake of the assessment results.